2020
DOI: 10.4314/acsj.v28i1.18s
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of labour among pig farmers in northern Uganda

Abstract: In many sub-Saharan countries, pig (Susscrofa domesticus) production is increasingly an important food security and income generating activity for smallholder farmers. This is attributed to the high prospects for vigilance of the pork market, driven by urbanisation, population growth and dietary transition towards more animal protein per capita. Therefore, increasing pig production is one of the viable pathways to get smallholder farmers out of poverty and food insecurity. Although there are extensive studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The present research explored, first, the EL-IWBs relationship, and second, the existence of IWBs with regard to the support provided by the organization (POS). Evidence from this study support a strong-positive and significant relationship between EL and IWBs, which is consistent with the works of Mugonya et al (2020), Özsungur (2019), Ahmad et al (2021) and Javed et al (2020). Also, this study established that a supportive environment within the organization enhances ethical leader's effectiveness in promoting IWBs, confirming suitability of the contingency theory to successful realization of IWBs.…”
Section: Theoretical Implicationssupporting
confidence: 89%
See 3 more Smart Citations
“…The present research explored, first, the EL-IWBs relationship, and second, the existence of IWBs with regard to the support provided by the organization (POS). Evidence from this study support a strong-positive and significant relationship between EL and IWBs, which is consistent with the works of Mugonya et al (2020), Özsungur (2019), Ahmad et al (2021) and Javed et al (2020). Also, this study established that a supportive environment within the organization enhances ethical leader's effectiveness in promoting IWBs, confirming suitability of the contingency theory to successful realization of IWBs.…”
Section: Theoretical Implicationssupporting
confidence: 89%
“…Based on SET (Blau, 1964), we argue that supervisor and subordinate relationships are dependent on reciprocity norms. Consequently, prior studies have found a significant link between EL and IWBs (Kasule et al, 2015;Mugonya et al, 2020;Zahra and Ajmal, 2017). Based on these theoretical insights, we propose that: H1.…”
Section: Theory and Hypotheses Development Ethical Leadership And Emp...mentioning
confidence: 96%
See 2 more Smart Citations